Correction to: characterizing active transportation mechanisms for free fatty acids and antibiotics in Synechocystis sp. PCC 6803 - Matthew P. A. Bellefleur; Soo-Young Wanda; Roy Curtiss III (BMC Biotechnology, 2019)
Following publication of the original article [1], the author reported that the gene/protein names of slr2131 and sll0180 were swapped in the Discussion section. The details of the correction are mentioned below: